Motor function recovery of people of mature years after stroke by means of physical rehabilitation - Khristova T.E (Kharkov National Pedagogical University, 2013)
The results of applying the complex technology of physical rehabilitation are described for patients with cerebral ischemic stroke during the phase of in-patient rehabilitation. The experiment involved 36 male patients aged 45-50 years. The rehabilitation program included treatment by changing position, complex of therapeutic gymnastics (based on sanogenetic approach to the problem of motor function recovery in accordance with the stages of postnatal ontogenesis), magnetic therapy, thermotherapy of large joints of the affected extremities. Findings show that the use of the mentioned methods of treatment leads to increase of the range of motion in the hip and shoulder joints: passive of 15-20%, and active of 10-30%, muscle strength of 10-30%, improvement of motor activity indices (scale of Bobaht) and quality of life (scale of Barthel).